Data Localization in Vietnam: An Introduction of the 2026 Regulatory Framework - Pham Duy Nghia (Proceeding International Conference Restructuring and Transforming Law, 2026)
As Vietnam accelerates its digital transformation, the legal framework governing data sovereignty has undergone a significant overhaul. This paper examines the evolution of data localization requirements from the initial Law on Cybersecurity (2018) and Decree 53/2022/ND-CP to the newly implemented Personal Data Protection Law (PDPL) and the Law on Cybersecurity 2025, effective as of early 2026.The study analyzes the specific categories of data subject to local storage-including personal information, user-generated logs, and relationship data-and the conditions under which foreign service providers must establish a local branch or representative office. Furthermore, the paper evaluates the practical challenges faced by multinational corporations in aligning global data strategies with Vietnam's "limited model" of data governance, which prioritizes national security and digital sovereignty. By comparing these local mandates with international standards like the GDPR, this research provides strategic insights for legal compliance and policy development in one of Southeast Asia's fastest-growing digital economies